WISATA DESA BERBASIS LAHAN RAWA DI DESA HAMBUKU TENGAH - Hasanah, Yuzhirna Najmi; Anhar, Pakhri (JURNAL TUGAS AKHIR MAHASISWA LANTING, 2021)
Swamp Based Village Tourism in Central Hambuku Village is a recreation area that presents attractions in the form of customs and daily life of the people of Central Hambuku Village in the past and is a place of education for swamps as the largest natural potential in the Village of Central Hambuku. This tour aims to become a swampy tourist attraction that can develop the potential of the village to improve the economy of the Central Hambuku Village community. The development of village potential as a tourist attraction requires an analysis of the potential that can be exploited, through analysis-synthesis methods and the concept of memory is expected to explore the potential of existing villages to create a place for recreation and education of swamps as well as to give the impression and experience of life in the village.